Homestay Online Booking and Management System - Yang, Jian Yu (2012)
The objective of this paper is to discuss Homestay Online Booking and Management System develops in web-based application.It is based on first come first serve concept. This system is develops to simplify booking process but also develop a searching and database synchronization.The design of this system included system interface design and database design.Flow chart,use block diagram are use for represent flowing process will occur when user interact with the system.However,the expected result shall be planning from now to reduce the risk taken.